Predictive influence of personality types on truancy behaviours among undergraduates in Osun State, Nigeria - O. Alebiosu Yejide; A. Jimoh Basit; O. Awosanya Olabi (The Open University of Sri Lanka, 2024)
There has been an increased interest in the study of human personality approach of traits as it concerns education, learning, academic achievement, emotional intelligence, and decision making among others. This paper attempted a descriptive and inferential investigation on the existence of truancy behaviours, the predictive influence of personality traits on truancy behaviours, and examined the moderating impact of gender on truancy behaviours among undergraduates in Osun state, Nigeria. Three (3) universities were purposively selected in Osun state because most universities were shut down due to industrial action by the academic staff union. A total enumeration technique was adopted to gather two hundred (200) undergraduates from the selected universities. The composition showed that one hundred and seven (107) of these respondents were males while ninety-three (93) were females. Two research questions and one hypothesis were raised in the study. The study gathered data using the Truancy and Personality Traits scale (T&PTs) developed by the researcher alongside the Personality Traits Inventory, IPIP BigFive factor Markers by Goldberg (1993) with reliability value of 0.71 and 0.84 respectively. The results showed that: truancy behaviours exist among undergraduates; personality traits are significant predictors of truancy behaviours with agreeableness personality traits as the most predictive personality traits; and gender was established as a critical factor in truancy behaviours among undergraduates. Study recommended that school counsellors, social workers. school management and psychologists should intensify their efforts in using social learning and other behaviour therapies to ameliorate truancy and other class attendance disruptive behaviours among undergraduates.